MODEL KOMUNIKASI WIRAUSAHA, PEMBELAJARAN WIRAUSAHA, SIKAP KEWIRAUSAHAAN, DAN KINERJA USAHA KECIL - Muhammad Rakib (Universitas Negeri Malang, 2016)
Abstract: Entrepreneurial Communication Model, Entrepreneurship Education, Entrepreneurship Attitude, and Small Bussiness Performance. This study tries to describe the influences of the model of entrepreneurship communication, entrepreneurship education, and entrepreneurship attitude on the performace of small business of wood furniture in Parepare. The sample taken is 140 owners of small business of wood furniture in Parepare and data are collected by using questionnaire, observations, interviews, and documentation study. Data were analyzed by using Structural Equation Modeling (SEM). The findings show that model of entrepreneurship communication, entrepreneurship education and entrepreneurship attitude affects significantly the performance of small businesses. This has implication that in order to predict the performance of small business, variables of interpreneurship model (openness, emphaty, support, positiveness, and the similarities), interpreneurship education (education and training, experience, and mentoring), and interpreneurship attitude (high discipline and commitment, honest behavior, risk taken, proactive, and good interpersonal) partially and simultaneously, contribute significantly to the real performance of small business. Abstrak: Model Komunikasi Wirausaha, Pembelajaran Wirausaha, Sikap Kewirausahaan, dan Kinerja Usaha Kecil. Tujuan penelitian ini adalah untuk menjelaskan pengaruh model komunikasi wirausaha, pembelajaran wirausaha, dan sikap kewirausahaan terhadap kinerja usaha kecil meubel kayu di Kota Parepare. Penelitian ini mengambil sampel sebanyak 140 pemilik usaha kecil meubel kayu di Kota Parepare dengan menggunakan kuesioner, observasi, wawancara, dan dokumentasi untuk mengumpulkan data. Teknik analisis data yang digunakan adalah Structural Equation Modeling (SEM). Temuan penelitian menunjukkan bahwa model komunikasi wirausaha, pembelajaran wirausaha, dan sikap kewirausahaan berpengaruh secara signifikan terhadap kinerja usaha kecil. Hal ini membawa implikasi bahwa untuk memprediksi pembentukan kinerja usaha kecil harus diperhitungkan besaran variabel model komunikasi wirausaha, pembelajaran wirausaha, dan sikap kewirausahaan.